Screen Time and Toddlers: New Evidence on Potentially Negative Effects. Issue 4 (July 2020) - Beal, Judy A.
Abstract : As more evidence becomes available about the negative effects of screen time for young children, pediatric nurses can help parents develop a family plan to minimize risk from exposure to excessive screen time. Our pediatric nursing expert, Dr. Beal, explains the new evidence on screen time and toddlers.